Bibliometric Analysis of Islamic Education Curriculum Research: Mapping Intellectual Structure, Thematic Trends, and Global Collaboration Patterns - Tajul Umam; Seipah Kardipah (Edusoshum : Journal of Islamic Education and Social Humanities, 2026)
Islamic education curriculum research has expanded significantly over the past decade, yet a comprehensive bibliometric mapping of its intellectual structure remains scarce. This study aims to map the intellectual landscape, primary thematic clusters, and global collaboration networks of Islamic curriculum research indexed in the Scopus database from 2016 to 2026. Employing a quantitative bibliometric design, this study analyzed 494 peer-reviewed English-language journal articles retrieved using Boolean keyword search strategies. Data were processed using VOSviewer (version 1.6.20) for co-keyword network visualization, overlay, and density analysis, and supplemented by Scopus analytical tools. Results indicate that Indonesia is the dominant contributor with 323 publications (65.4%), followed by Malaysia. Publication output surged significantly from 2020 onward, correlating with the global COVID-19 pandemic. Eight primary thematic clusters were identified, centering on religious moderation, curriculum integration, digital learning, pesantren and madrasah education, and artificial intelligence. The study concludes that the field is rapidly growing, with Southeast Asia emerging as the principal hub of knowledge production. However, significant gaps remain, particularly in longitudinal curriculum impact studies and cross-national comparative research. These findings provide a strategic roadmap for future research directions in Islamic education.